2022
DOI: 10.1002/ange.202209350
|View full text |Cite
|
Sign up to set email alerts
|

High‐Entropy Prussian Blue Analogues and Their Oxide Family as Sulfur Hosts for Lithium‐Sulfur Batteries

Abstract: The introduction of high-entropy into Prussian blue analogues (PBAs) has yet to attract attention in the field of lithium-sulfur battery materials. Herein, we systematically synthesize a library of PBAs from binary to high-entropy by a facile coprecipitation method. The coordination environment in PBAs is explored by X-ray absorption fine structure spectroscopy, which together with elemental mapping confirm the successful introduction of all metals. Importantly, electrochemical tests demonstrate that high-entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…A 1 wt.% Au loading was required to ensure sufficient Au species supplied under the experimental conditions, to avoid possible errors caused by low loading. The metal content was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) [ 21 ] and detected at approximately 0.98 wt.% Au mass, basically matching the expected 1 wt.% Au loading ( Table 1 ). The Au loading was further verified by the X-ray fluorescence (XRF) results, and 1.07 wt.% Au loading was gained.…”
Section: Resultsmentioning
confidence: 78%
“…A 1 wt.% Au loading was required to ensure sufficient Au species supplied under the experimental conditions, to avoid possible errors caused by low loading. The metal content was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) [ 21 ] and detected at approximately 0.98 wt.% Au mass, basically matching the expected 1 wt.% Au loading ( Table 1 ). The Au loading was further verified by the X-ray fluorescence (XRF) results, and 1.07 wt.% Au loading was gained.…”
Section: Resultsmentioning
confidence: 78%
“…They found that the high-entropy PBA can not only inhibit the shuttle effect by serving as a polysulfide immobilizer but also as catalyst to promote polysulfide conversion, thereby boosting its Li-S battery performance. 104 Although cation regulation was widely used…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…They found that the high-entropy PBA can not only inhibit the shuttle effect by serving as a polysulfide immobilizer but also act as a catalyst to promote polysulfide conversion, thereby boosting its Li–S battery performance. 104 Although cation regulation has been widely used so far, the anion regulation certainly provides a new route for the property adjustment for various applications such as batteries, electrolytes, etc. , and more novel high-entropy compounds can be expected in future.…”
Section: Composition Regulationsmentioning
confidence: 99%
“…Since reported in the 1990s, MOF‐based materials have been well developed in the past three decades and have broad application prospects in many fields such as adsorption, separation, sensors, biomedicine, catalysis, and electrochemical energy storage, which stems from their diverse crystalline structures. [ 73–81 ] MOFs are constructed by linking metal nodes (metal ions or clusters) with organic linkers ( Figure 3 a), and some representative metal node configurations and organic linkers (mainly carboxylic acids or nitrogenous ligands) are shown in Figure 3b,c. [ 82 ] Such coordination enables a pore space to appear in the structural unit of MOFs (Figure 3a), and the porous structure is further formed with periodic combination, resulting in large specific surface areas of MOFs in the range of 1000–10000 m 2 g −1 .…”
Section: Structural Advantages Of Mof‐based Materialsmentioning
confidence: 99%
“…Since reported in the 1990s, MOF-based materials have been well developed in the past three decades and have broad application prospects in many fields such as adsorption, separation, sensors, biomedicine, catalysis, and electrochemical energy storage, which stems from their diverse crystalline structures. [73][74][75][76][77][78][79][80][81] MOFs are constructed by linking metal nodes [57] Copyright 2018, Elsevier. Separator part: Reproduced with permission.…”
Section: Structural Advantages Of Mof-based Materialsmentioning
confidence: 99%